2022
DOI: 10.7759/cureus.32578
|View full text |Cite
|
Sign up to set email alerts
|

Opsoclonus Myoclonus Syndrome in a Case of Severe Acute Malnutrition in Children: A Case Report

Abstract: Opsoclonus myoclonus syndrome (OMS) is a rare (1 in 10 million people per year) but nonfatal autoimmune disorder characterized by involuntary oscillating eye movements, multifocal muscular jerky movements, severe ataxia, and neuropsychological and behavioral changes. It usually manifests as a paraneoplastic condition but has other etiologies also. To the best of our knowledge, this is the first case of OMS seen in a patient with severe acute malnutrition (SAM). Parents brought a three-year-old female child wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…OMAS also has a para-infectious etiology; studies have reported its association with Epstein–Barr virus [ 12 ], hepatitis C virus [ 13 ], rotavirus [ 14 ], adenovirus [ 15 ], enterovirus [ 16 ], rhinovirus, RSV [ 17 ], human herpesvirus 6 [ 18 ], malaria [ 19 ], and COVID-19 [ 20 ]. Some studies have shown the development of OMAS to be secondary to immune reconstitution after highly active antiretroviral therapy (HAART) for HIV [ 21 ] and severe acute malnutrition [ 22 ], while its association with type 1 diabetes mellitus [ 23 , 24 ] and Aicardi–Goutières syndrome [ 25 ] has also been reported.…”
Section: Reviewmentioning
confidence: 99%
“…OMAS also has a para-infectious etiology; studies have reported its association with Epstein–Barr virus [ 12 ], hepatitis C virus [ 13 ], rotavirus [ 14 ], adenovirus [ 15 ], enterovirus [ 16 ], rhinovirus, RSV [ 17 ], human herpesvirus 6 [ 18 ], malaria [ 19 ], and COVID-19 [ 20 ]. Some studies have shown the development of OMAS to be secondary to immune reconstitution after highly active antiretroviral therapy (HAART) for HIV [ 21 ] and severe acute malnutrition [ 22 ], while its association with type 1 diabetes mellitus [ 23 , 24 ] and Aicardi–Goutières syndrome [ 25 ] has also been reported.…”
Section: Reviewmentioning
confidence: 99%
“…The disease has a prevalence of around 1 per 100,000 persons. It primarily affects the motor neurons of the anterior horn cells of the central nervous system [ 1 ]. These motor neurons are responsible for skeletal muscle activity in the body [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 5% includes other mutations in different locations. This gene is located in the telomeric regions of chromosome 5q13 and is important for maintaining the integrity of motor neurons [ 1 ]. An identical gene known as SMN2 is hypothesized to be involved in the disease as well.…”
Section: Introductionmentioning
confidence: 99%